2021
DOI: 10.1021/acsanm.1c03173
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride/Polyaniline Nanocomposites for Anticorrosive Waterborne Epoxy Coatings

Abstract: The hexagonal boron nitride (h-BN) nanosheets have been used as nanofillers to improve the barrier properties of the waterborne epoxy (WEP) coatings. However, the h-BN nanosheets tend to agglomerate, which limits their anticorrosion applications. In this paper, the h-BN/polyaniline (h-BN/PANI) nanocomposites were prepared by the in situ polymerization of aniline on the surfaces of the h-BN nanosheets, which were further used to improve the anticorrosion performance of the WEP coatings. The structures of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 75 publications
3
21
0
1
Order By: Relevance
“…Yi et al, in their study on size-selected BNNS coating on a polymer, concluded that larger BNNS (∼21.4 μm 2 ) greatly enhanced the corrosion resistance of the polymer. Hexagonal BN’s proactive anticorrosive property is directly correlated with its surface morphology and area. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yi et al, in their study on size-selected BNNS coating on a polymer, concluded that larger BNNS (∼21.4 μm 2 ) greatly enhanced the corrosion resistance of the polymer. Hexagonal BN’s proactive anticorrosive property is directly correlated with its surface morphology and area. …”
Section: Introductionmentioning
confidence: 99%
“…Bulk, free-standing 1D boron nanotubes (BNNTs) fabricated as 100% BNNT and oriented randomly in-plane are commercially available as BNNT buckypaper (BP). They are analogous to carbon nanotubes but offer multifunctional advantages, including piezoelectricity, electrical insulation, high-temperature stability, and neutron absorption. , Compared to 2D hBN nanoplatelet (BNNP), 1D BNNT is arranged randomly into a porous 3D structure and offers a substantially greater surface area. Previous research studies concluded that hBN with a high surface area offers increased corrosion resistance due to higher interfacing with the underlying material. Yet, BNNTs are not recognized as corrosion-inhibiting additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductive polymer (CP) coatings, including polyaniline (PANI), polypyrrole (PPy), and polythiophene (PTH), are potential candidates for protecting metallic bipolar plates from corrosion and reducing resistance due to their good corrosion resistance, high stability, simple synthetic process, and other characteristics 7–10 . However, the limitations of CP coating, including its anion‐exchange properties, porous structure, and irreversible depletion of the charge stored in it, still need to be solved 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Опубликованы работы по использованию его композитов в качестве материала для коррозионной защиты. Описано использование композитов на основе графена и полимера Nafion [5], на основе графена, нитрида бора и полианилина [6]. Графен также находит применение в качестве носителя катализатора в системах электрохимического преобразования энергии [7,8].…”
unclassified